2010
DOI: 10.1111/j.1365-294x.2010.04557.x
|View full text |Cite
|
Sign up to set email alerts
|

The earliest stages of adaptation in an experimental plant population: strong selection on QTLS for seed dormancy

Abstract: Colonizing species may often encounter strong selection during the initial stages of adaptation to novel environments. Such selection is particularly likely to act on traits expressed early in development since early survival is necessary for the expression of adaptive phenotypes later in life. Genetic studies of fitness under field conditions, however, seldom include the earliest developmental stages. Using a new set of recombinant inbred lines, we present a study of the genetic basis of fitness variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
200
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(206 citation statements)
references
References 41 publications
6
200
0
Order By: Relevance
“…The phenomenon that the maternal environment during seed development and maturation determines the germination phenology of Arabidopsis and other species is well-established knowledge (Kugler, 1951;Gutterman, 1980Gutterman, /1981Munir et al, 2001). However, as a major advance, we now know from ecological work with Arabidopsis (Huang et al, 2010;Moyers and Kane, 2010;Chiang et al, 2011;Barua et al, 2012;Kronholm et al, 2012) that natural genetic variation at the DOG1 locus is a major determinant for the local adaptation to novel environments, and we also know that the maternal environment controls DOG1 gene expression during seed maturation. For example, low temperature during seed maturation causes increased DOG1 gene expression and deeper primary dormancy of mature seeds (Chiang et al, 2011;Kendall et al, 2011;Nakabayashi et al, 2012).…”
Section: Discussion Spatiotemporal Maturation Patterns In L Papillosmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon that the maternal environment during seed development and maturation determines the germination phenology of Arabidopsis and other species is well-established knowledge (Kugler, 1951;Gutterman, 1980Gutterman, /1981Munir et al, 2001). However, as a major advance, we now know from ecological work with Arabidopsis (Huang et al, 2010;Moyers and Kane, 2010;Chiang et al, 2011;Barua et al, 2012;Kronholm et al, 2012) that natural genetic variation at the DOG1 locus is a major determinant for the local adaptation to novel environments, and we also know that the maternal environment controls DOG1 gene expression during seed maturation. For example, low temperature during seed maturation causes increased DOG1 gene expression and deeper primary dormancy of mature seeds (Chiang et al, 2011;Kendall et al, 2011;Nakabayashi et al, 2012).…”
Section: Discussion Spatiotemporal Maturation Patterns In L Papillosmentioning
confidence: 99%
“…Several recent publications clearly demonstrate that in Arabidopsis, QTLs with large effects on fitness colocalize with QTLs for field germination timing and seed dormancy (Huang et al, 2010;Moyers and Kane, 2010;Chiang et al, 2011;Barua et al, 2012;Kronholm et al, 2012). Germination phenology is under intense, geographically variable, natural selection in Arabidopsis, since it is the major determinant of fitness during the earliest stages of colonization (Huang et al, 2010;Moyers and Kane, 2010;Chiang et al, 2011;Barua et al, 2012;Kronholm et al, 2012). It is also evident that QTLs including DOG1 determine the phenotypic plasticity of seed germination/dormancy responses already on the mother plant in interaction with environmental factors such as seed maturation photoperiod and temperature.…”
Section: Discussion Spatiotemporal Maturation Patterns In L Papillosmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural Arabidopsis accessions show considerable differences in seed dormancy, which can for an important part be explained by a quantitative trait locus located at the DOG1 gene, both in laboratory (Bentsink et al, 2010) and field experiments (Huang et al, 2010). In addition, it was shown that differences in DOG1 expression between Arabidopsis accessions contribute to geographical variation in dormancy and germination (Chiang et al, 2011).…”
Section: Dog1 Expression and Protein Levels In Freshly Harvested Seedmentioning
confidence: 99%
“…Selection experiments under contrasting CO 2 or simulated seasonal conditions have identified distinct genetic responses in Arabidopsis that account for evolutionary changes in flowering time depending on the selection environment (Springer et al 2008;Scarcelli & Kover 2009). The fitness consequences of dormancy characteristics differ between seeds dispersed in autumn and those in spring, and seasonal QTL involved in dormancy response and fitness can also be identified (Donohue et al 2005;Huang et al 2010). Thus, knowledge at the genetic level of the basis of phenological traits, the amount of natural variation in these traits, the effect of season on expression of these traits and their fitness consequences in seasonal environments will be necessary to achieve more accurate predictions of the integrated life-history responses of plants to novel environments.…”
Section: (D) Model Limitations and Future Extensionsmentioning
confidence: 99%